Complement Regulator CD46 Transcripts are Associated with Progression of Chronic Antibody Mediated Rejection and Recurrent IgA Nephropathy. (July 2018) - Cernoch, Marek; Kollar, Marek; Hruba, Petra; Lodererova, Alena; Slatinska, Janka; Honsova, Eva; Viklicky, Ondrej
Abstract : Introduction: The complement system activation and regulation have been linked to post-transplant pathologies including chronic antibody mediated rejection (CAMR) and the recurrence of IgA nephropathy (ReIgAN). The aim of this study was to evaluate the long term outcome of kidney transplantation after histological diagnosis of CAMR and ReIgAN and to decipher the relationship of complement-related transcripts to the progression of graft dysfunction. Methods: In this retrospective single center study, 93 patients with histological proven CAMR and 57 patients with histological proven ReIgAN were enrolled. A total of 51 available snap frozen kidney biopsy samples (26 CAMR and 25 ReIgAN) were used for RNA isolation and gene expression analysis by RT-qPCR of 11 genes connected to complement cascade and regulation: C3, C5, CD46, CD55, CD59, C4BP, CFH, CFI, CFP, CR1 and C1-INH . The complement genes were selected both for their significance in the complement cascade and the existing evidence of their involvement in pathological processes of CAMR and ReIgAN. Immunohistochemistry was used to evaluate the presence of proteins CD46 and C5 on cell surface from formalin-fixed paraffin-embedded kidney tissue, stained with appropriate antibodies. Results and Discussion: Median time from transplantation to biopsy was comparable in both groups (6 years in CAMR patients and 6 years and 9 months in ReIgAN). Interestingly, there were no significant differences in kidney graft survival since transplantation and diagnostic biopsy between both groups (Fig 1, Fig. 2). CAMR was associated with significantly higher intragraft transcripts of C3, CD59 and C1-INH compared to ReIgAN (p<0.05). A statistically significant correlation between increased intrarenal CD46 expression and decreased graft survival in CAMR patients was found (p<0.01, r=−0.508). Similarly, C3 transcripts correlated significantly with lower eGFR in CAMR group (p<0.05, r=−0.417). There were also significant correlations of both CD46 and CFI transcripts with lower eGFR in ReIgAN group (p<0.05, r=−0.401 and p<0.05, r=−0.442, respectively). Immunohistochemistry did not reveal an association between the presence of CD46 and C5 proteins on cell surface and the transcript levels of those genes. Conclusion: The long-term graft survival of patients with CAMR is similar to ReIgAN. The complement regulator CD46 transcripts are likely to be associated with the progression of CAMR as well as ReIgAN. Ministry of Health, Czech Republic - conceptual development of research organization („Institute for Clinical and Experimental Medicine – IKEM, IN 00023001"). Figure. No caption available. Figure. No caption available.